Compound heterozygosity of a paternal submicroscopic deletion and a maternal missense mutation in POR gene: Antley‐bixler syndrome phenotype in three sibling fetuses. Issue 7 (11th March 2016) - Tzetis, Maria; Konstantinidou, Anastasia; Sofocleous, Christalena; Kosma, Konstantina; Mitrakos, Anastasios; Tzannatos, Christina; Kitsiou‐Tzeli, Sofia
Abstract : Background: Antley‐Bixler syndrome (ABS) is an exceptionally rare craniosynostosis syndrome that can be accompanied by disordered steroidogenesis, and is mainly caused by mutations in the POR gene, inherited in an autosomal recessive manner. Here we report the prenatal and postmortem findings of three sibling fetuses with ABS as a result of compound heterozygosity of a paternal submicroscopic deletion and a maternal missense mutation in the POR gene. Methods: Prenatal ultrasound and postmortem examination were performed in three sibling fetuses with termination of pregnancy at 22, 23, and 17 weeks of gestation, respectively. Molecular analysis of fetus 2 and 3 included (a) bidirectional sequencing of exon 8 of the POR gene after amplification of the specific locus by polymerase chain reaction, to detect single nucleotide variants (SNVs) and (b) high resolution comparative genomic hybridization (CGH) positive single nucleotide polymorphism array CGH (aCGH) analysis to detect copy number variants (CNVs), copy neutral areas of loss of heterozygosity and uniparental disomy. Results: The diagnosis of ABS was suggested by the postmortem examination findings. The combination of the POR gene molecular analysis and aCGH revealed a compound heterozygous genotype of a maternal SNV (p.A287P) and a paternal CNV (NC_000007.13:g.(?_75608488)_(75615534_?)del). Conclusion: To the best of our knowledge, these sibling fetuses add to the few reported cases of ABS, caused by a combination of a SNV and a CNV in the POR gene. The detailed description of the pathologic and radiographic findings of second trimester fetuses affected with ABS adds novel knowledge concerning the early ABS phenotype, in lack of previous relevant reports. Birth Defects Research (Part A) 106:536–541, 2016. © 2016 Wiley Periodicals, Inc.